Teacher correction versus peer-marking (2004)
Written language is undoubtedly more often used than oral language in a variety of contexts, including both the professional and academic life. Consequently, developing strategies for correcting compositions and improving students’ written production is of vital importance. This article describes an experiment aimed at assessing the two most widely used methods of correction for compositions –traditional teacher correction and peer marking and their effect on the frequency of errors. Data was collected by asking students to write and revise a text. Statistical tests were performed to analyse it. At the end of the experiment, it was found that no significant difference in efficiency existed between the two methods, contradicting expectations (cf. Davies, 2002; Levine et al., 2002 and Ward, 2001). Key words: English-Teaching, Foreign Language-Teaching Writing, Evaluation, Assessment El lenguaje escrito es sin duda usado con más frecuencia que el lenguaje oral en una variedad de situaciones o contextos, incluyendo tanto la vida profesional como la académica. En consecuencia, el desarrollo de estrategias para corregir composiciones y mejorar la producción escrita de los estudiantes es de suma importancia. Este artículo describe un experimento cuyo objetivo es evaluar los dos métodos más usados para la corrección de composiciones, la corrección tradicional por el maestro y la corrección por revisión de pares, con respecto a su efecto en la frecuencia de errores. Se recogió información haciendo que estudiantes escribieran y revisaran un texto y sobre esos textos se aplicaron pruebas estadísticas para analizar los errores. Contrario a lo esperado, al final del experimento, no se encontró ninguna diferencia significativa entre los resultados encontrados por los dos métodos, (cfr. Davies, 2002; Levine et al., 2002 y Ward, 2001). Palabras claves: Inglés-Enseñanza, Idioma Extranjero-Enseñanza, Composición, Evaluación